1973
DOI: 10.3109/15563657308990540
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Toxicologic Assessment of the Neurologic Effect of Lead in Sheep

Abstract: The behavioral toxlcologst uses the techmques of ammal behavior to study the selectlve tomcity of neuropolsons [ 11. Ruffin [ 2 ) proposed the use of functional testrng in experimental ennronmentll torfcology r e l a h g to industrial health. Van Gelder [ 31 recently discussed the role of behavioral toxlcology m eluadating possible adverse health effects of environmental contammuis.Lead 19 a neurotoscant that 1s presently adversely affecting the health of humans and e s p e w d y children. As more c o m m m t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1974
1974
1998
1998

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Our sheep sometimes responded in this way, but at times even control subjects would respond excessively during the interval (Figure 7). Van Gelder et al (1973) used two operant procedures to examine lead intoxication in sheep, and they found that an FI schedule was not sensitive to the toxic insult.…”
Section: Discussionmentioning
confidence: 99%
“…Our sheep sometimes responded in this way, but at times even control subjects would respond excessively during the interval (Figure 7). Van Gelder et al (1973) used two operant procedures to examine lead intoxication in sheep, and they found that an FI schedule was not sensitive to the toxic insult.…”
Section: Discussionmentioning
confidence: 99%
“…Our use of an auditory signal detection task which required sheep to depress a pedal within 5 sec after a 0.1-sec duration of 5 kHz tone to assess the neurologic effects of lead has been reported (11). Adult sheep given oral lead at 100 mg/kg-day for 9 weeks performed significantly poorer on the auditory signal detection task for a food reinforcement, but this effect was associated with the anorexia of acute toxicosis.…”
mentioning
confidence: 99%
“…Performance after 4 weeks of exposure was significantly less stable in the exposed sheep than in the controls. Van Gelder et al (1973) also reported that daily oral doses of 120 and 230 mg lead for 27 weeks did not alter the performance of mature sheep on a fixed interval schedule of reinforcement behavioral task.…”
Section: Behavioral Effects Of Lead In Animalsmentioning
confidence: 99%
“…Weir and Hine (1970) reported that goldfish exposed to sublethal lead concentrations of 10 ppm or less in their aquatic environment for 24 and 48 hr showed impaired performance on a conditioned avoidance task. Van Gelder et al (1973) reported increasingly poor performance on an auditory signal detection behavioral task by mature sheep receiving daily oral doses of 100 mg lead/kg. The fewer number of correct responses by the lead exposed sheep was believed to be a manifestation of clinical lead tox icosis.…”
Section: Behavioral Effects Of Lead In Animalsmentioning
confidence: 99%